Evaluation of user’s thermal perception and satisfaction towards indoor environmental quality - Kwon, Minyoung (A+BE | Architecture and the Built Environment, 2020)
Chapter 3 compared the building characteristics of renovated offices such as façade types and the HVAC system and energy consumption with different units. These physical building characteristics do not only contribute to energy performance but also to the indoor environment. For user satisfaction studies, a comfortable indoor environment is one of the primary conditions of the working environment. Therefore, it is important to identify the impact of indoor climate on user satisfaction in different office buildings (technical attributes of renovated office buildings). The purpose of this chapter is to identify the impact of indoor climate on user satisfaction, comparing how much they are satisfied with the indoor climate to temperature and relative humidity and how much the users can adapt the certain temperature. Section 4.2 presents the data collection for 2 weeks in three seasons: summer, winter, and the intermediate season. Monitored indoor climate such as temperature, and relative humidity is compared in section 4.3. Section 4.4 compares the occupants’ thermal sensation, preference and satisfaction with physical measurements are compared in section 4.3. Lastly, the predicted optimal thermal conditions, and limitations are discussed in section 4.5.